2022
DOI: 10.1172/jci.insight.156669
|View full text |Cite
|
Sign up to set email alerts
|

Serological profiling reveals hsa-miR-451a as a possible biomarker of anaphylaxis

Abstract: Background: There is a need to support the diagnosis of anaphylaxis by objective markers. miRNAs are promising non-coding RNA species that may serve as serological biomarkers, but their use in diagnosing anaphylaxis has not been systematically studied. We aimed to comprehensively investigate serum biomarker profiles (proteins, lipids, and miRNAs) to support the diagnosis of anaphylaxis.Methods: Adult patients admitted to the emergency room with a diagnosis of anaphylaxis (< 3 hours) were included. Blood sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…Increased serum levels of miR-101-3p were observed also in neonatal sepsis ( 57 ). MiR-451a, mostly expressed in blood cells and released in extracellular vesicles, attenuates type I IFN and IL-6 responses ( 58 , 59 ) and was reported to progressively decrease with COVID-19 severity ( 19 21 ). MiR-155-5p plays a key role in the homeostasis and function of the immune system ( 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increased serum levels of miR-101-3p were observed also in neonatal sepsis ( 57 ). MiR-451a, mostly expressed in blood cells and released in extracellular vesicles, attenuates type I IFN and IL-6 responses ( 58 , 59 ) and was reported to progressively decrease with COVID-19 severity ( 19 21 ). MiR-155-5p plays a key role in the homeostasis and function of the immune system ( 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, a study in a pediatric population with foodinduced anaphylaxis has shown increased circulating serum levels of miR-21-3p and miR-487b-3p [181]. Similarly, other evidences propose miR-451a as the most relevant biomarker in adult blood samples [88].…”
Section: Micrornasmentioning
confidence: 93%
“…Years later, those are considered a blend of prostaglandins and cysteinyl-leukotrienes released mainly through MC activation [35,86]. In addition, some of these molecules have been considered as valuable biomarkers in anaphylaxis [84,87,88]. Interestingly, non-steroidal anti-inflammatory drugs has been related with the increase of PGE2 and the production and overexpression of adenosine receptor 3 (A3) [89,90].…”
Section: Sphingosine-1-phosphate (S1pmentioning
confidence: 99%
See 2 more Smart Citations